Pengaturan Hukum Usaha Mikro Kecil dan Menengah (UMKM) berdasarkan Keadilan Ekonomi - Ramadhana, Widodo (Maliyah : Jurnal Hukum Bisnis Islam, 2023)
Indonesia is a country with a contribution of 60% coming from MSMEs. So in Indonesia itself, MSMEs are business units that play a big role in the national economy to increase the country's foreign exchange. For this reason, it is necessary to study the development of MSMEs to increase Indonesia's economic growth and the concept of protecting MSMEs based on an economic justice approach. The type of research used in this writing is normative juridical which is descriptive analysis. The data collection technique used is documentation of data. The development of MSMEs is one of the government's efforts as ruler to increase investment and create job opportunities. These efforts are contained in Law no. 11 of 2020 concerning Job Creation and Government Regulation Number 7 of 2021 concerning the Development, Protection and Strengthening of Small Cooperatives and Businesses. The concept of a fair legal protection mechanism to ensure the inequality of the free market economic system which creates a gap between large entrepreneurs and small entrepreneurs, especially MSMEs.